THE NEW URBAN CONCEPT OF HANSEATIC CITIES OF THE RIGA ARCHBISHOPRIC IN THE 13TH–14TH CENTURIES - Ozola, Silvija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
Bishop of Riga Albert established bishoprics and centers of spiritual life on the Southern Baltic Sea coast to subjugate the local population. Sacred buildings were the main architectural highlights of the urban environment. Later, Riga became the main military base for expansion in the Baltics, the economic base of the Teutonic Order, and the administrative center of the Archbishopric of Riga (1255–1562). On the Baltic Sea coast, new bishoprics began to be established in the lands of the subject Prussians. Important cities were involved in the Hanseatic League. Consequently, the concept of urban planning and construction changed in the 13th– 14th centuries. Research object: urban space of the Hanseatic League cities on the Prussian lands in the 13th–14th centuries. Research problem: sacral buildings changed urban aesthetics and the urban space of the Hanseatic cities, which has not been studied enough to preserve their identity. Research goal: analysis of the impact of churches for the citizenship parishes on the planning, visual image, and architectural-spatial development of the Hanseatic League cities in the lands of the subject Prussians. Novelty: analysis of common and local features of the structural evolution of the Hanseatic cities under the authority of the Archbishopric of Riga during the 13th and 14th centuries. Research methods: analysis of archive documents, projects, cartographic materials, and studies of published literature.